2023
DOI: 10.21134/pssa.v11i1.321
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fear on anti-vaccine conspiracy theories and behaviour against vaccination

Abstract: Pandemics are a global threat, with vaccination being the main weapon of control. Fear, an unpleasant emotional state caused by a threatening stimulus perception, is known to be behind inhibitory behaviours; being, with mistrust, the basis of anti-vaccine conspiracy theories (CTs). It would be appropriate to know the fear influence on these theories. In this way, a cross-sectional online survey was applied to 2.987 subjects, in a COVID-19 context, characterized by high levels of uncertainty and mistrust, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Both studies found a clear and significant association between fear of vaccination and vaccination intention, with the fear of vaccination emerging as a stronger predictor compared to hesitancy [8] or fear of the targeted disease [9]. A clear relationship has also been described between fear of vaccination and the self-report of conspiracy beliefs [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found a clear and significant association between fear of vaccination and vaccination intention, with the fear of vaccination emerging as a stronger predictor compared to hesitancy [8] or fear of the targeted disease [9]. A clear relationship has also been described between fear of vaccination and the self-report of conspiracy beliefs [24,25].…”
Section: Introductionmentioning
confidence: 99%